Influenza A Virus Surveillance in the Invasive American Mink (Neovison vison) from Freshwater Ecosystems, Northern Spain. (5th December 2016) - Gholipour, H.; Busquets, N.; Fernández‐Aguilar, X.; Sánchez, A.; Ribas, M. P.; De Pedro, G.; Lizarraga, P.; Alarcia‐Alejos, O.; Temiño, C.; Cabezón, O.
Summary: Influenza A viruses (IAVs) are negative‐sense, single‐stranded and segmented RNA viruses of the Orthomyxoviridae family that may cause acute respiratory disease in a wide range of birds and mammals. Susceptibility of several species within the family Mustelidae to IAVs has been reported as a result of natural or experimental infections. The objectives of this study were to assess whether free‐ranging American mink populations from Northern Spain were infected with IAV and try to define the role of this species in the epidemiology of IAV. Sera from 689 American mink from Northern Spain captured between 2011 and 2014 were tested for the presence of antibodies against IAVs using a commercial competition cELISA. Positive sera were further analysed with haemagglutination inhibition (HI) assay. Fifteen of the 689 (2.2%, 1.3–3.6 CI95% ) of the American minks analysed were ELISA positive. No significant differences were observed between years of capture, provinces, river basins, sexes or ages of the animals. All seropositive sera resulted negative to the panel strains used in the HI assay, showing that the most relevant strains circulating in swine, the most relevant avian subtypes (H5 and H7) and the H10N4 subtype isolated in minks have not been circulating in this free‐ranging exotic carnivore from Spain. In the light of these results, the free‐range American mink from Northern Spain do not seem to have an important role in the epidemiology of IAVs.